EFFECT OF TEPID SPONGE ON CHANGES IN BODY TEMPERATUR IN CHILDREN - Puspitasari, R.A. Helda; Handayani, Dwining; Nastiti, Ayu Dewi; Kusuma, Erik (Indonesian Journal of Community Health Nursing, 2022)
Introduction: Fever is a state of body temperature above normal as a result of an increase in temperature control in the hypothalamus. Most children have fever due to thermoregulation in the hypothalamus. The purpose of literature review is to explore the effect of giving a water tepid sponge on reducing fever in children. Method: This study uses the literature review with article searches conducted on the electronic databases of Science Direct, Garuda and Google Schoolar. There were 543 articles on Science Direct, Garuda and Google Schoolar but only 10 articles that met all the inclusion criteria and were reviewed Results: There is an effect on reducing fever in children by using a water tepid sponge. Conclusion: Based on the results of a review of 10 literatures on reviewedthe characteristics of study respondents aged 1-12 years. Respondents who experienced hyperthermia/increased body temperature there was an influence of changes/decreased body temperature by giving water tepid sponge an averagerepeatedly so that the body temperature becomes 100% normal. The average temperature of children with fever in the 10 literatures is 38.5°C, the result with p value = 0.001 on the tepid water sponge which means that there is an effect of decreasing body temperature with the action of the water tepid sponge.